PENGARUH MEDIA VISUAL TIGA DIMENSI TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD MUHAMMADIYAH 6 PEKANBARU - Yati, Erni; Witri, Gustimal; Alpusari, Mahmud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: this research is a quasi experimental with non equivalent control group design based on how low students mathematics scores. The purpose of this research is to know the difference of the mathematics scores of students who learn by using three dimensional visual media with those who learn using two dimensional visual media. This research was executed in Muhammadiyah 6 elementary school Pekanbaru on the even semester of 2016/2017 study year. Subjects of this research were Muhammadiyah 6 elementary school 4th grade students with IVA students as control class and IVB students as experimental class. Early step of this research is by giving pretest to the control and experimental class. The next step is applying study methods using three dimensional visual media to experimental class and two dimensional visual media to control class. The last step is giving post test to control and experimental classes. Result of this research shows that there is a difference of significant increase of study results with 0.05 significant quality shown by average score of pretest taken by experiment class of only 54,96 increasing to 79,13 average scores of post test. With average gain of 0.54 (considered medium category). Meanwhile, control class average scores of pretest of 55, 67 only increasing to 64,33 on the post test, with the average gain of 0.05 (considered low category).Keywords: Three dimensional visual media, mathematics study scores.